Effect of Confucius' Pillow Elixir on Cognitive Ability of Agrypnia Mice and Its Mechanism. Issue 4 (February 2020) - Ren, Yumei; Sun, Ning; Chen, Wenyu; Chen, Yan; Ma, Mengge; Wang, Xiao; Meng, Yongli; Cao, Zhaoxia; Cai, Ruijuan; Ren, Shicheng; Liu, Xiaomei; Liang, Xuejiao; et al.
Abstract: Aim : To investigate the influence of Confucius' Pillow Elixir on cognitive ability of agrypnia mice and its mechanism. Methods : Twenty-four mice were randomly divided into normal group, model group, Confucius' Pillow Elixir group and Diazepam group. Mice were suffered from continuous sleep deprivation with improved multi-platform water environment sleep deprivation boxes. Normal group and model group were given the same amount of normal saline, Confucius' Pillow Elixir group was given Confucius' Pillow Elixir decoction and Diazepam group were given Diazepam. During the experiment, we need to observe and record the general state and body weight of each group of mice. The open-field experiment and Morris water maze were conducted. Gamma-aminobutyric acid (GABA) concentration in serum of mice was determined by Elisa. Results : In the open-field experiment, compared with the model group, the number of horizontal motion grids in the Confucius' Pillow Elixir group increased significantly, with statistical difference (P<0.05).In the Morris water maze positioning navigation test, compared with the model group, the escape latency of Confucius' Pillow Elixir group was significantly reduced, with statistical difference (P<0.01). Compared with the model group, the GABA concentration in Confucius' Pillow Elixir group was significantly decreased, with statistical difference (P<0.01).